Czapski samotny. Kilka refleksji o "Dziennikach wojennych" Józefa Czapskiego - Janiak, Agata (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2024)
Recenzja: J. Czapski, "Dziennik wojenny: (22 III 1942–31 III 1944)", odczytał J. S. Nowak, oprac. M. Nowak-Rogoziński, Warszawa 2022.